Emotion Distress and Self-Care Behavior in Type II Diabetes Mellitus Patients in Matsum, Medan, North Sumatera - Susy Hariaty Situmorang; Namora Lumongga Lubis; Kintoko Rochadi (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Diabetes mellitus (DM) is currently one of the major health problems in the world because it has an impact on declining productivity and quality of human resources. This disease also causes sufferers to experience a state of disability, loss of productivity, and become a burden for individuals, families and communities that can cause emotional distress in people with diabetes mellitus. The purpose of this study was to determine the effect of emotional distress on self-care behavior of people with type 2 diabetes mellitus at the Matsum Health Center.Subjects and Method: This study used a cross sectional design conducted at Matsum Health Center in Medan. The number of samples was 49 people and taken with non-probability sampling technique by quota sampling. The dependent variable was self-care behavior. The independent variable was emotional distress. Data were collected by questionnaires and analyzed using Chi square test.Results: Low emotional distress increases self-care behavior in patients with type 2 diabetes mellitus (OR= 11.33; 95% CI with p = 0.004).Conclusion: Low emotional distress increases self-care behavior in patients with type 2 diabetes mellitus.Keywords: Emotional distress, self-care behavior, diabetes.Correspondence: Susy Hariaty Situmorang. Masters Program in Public Health, Universitas Sebelas Maret. Email: susysitumorang88@gmail.com. Mobile: 081220230986.Journal of Health Promotion and Behavior (2019), 4(2): 153-158https://doi.org/10.26911/thejhpb.2019.04.02.08